(untitled) (Biological Sciences - PJSIR, 2022)
A diallel cross involving four rice cultivars; Basmati 370, Basmati 385,4048 and Basmati 198 was studied in the F I generation for anther length, IOO-anther weight, pollen grain size and percent filled spikelets. Both general combining ability (OCA) and specific combining ability (SCA) were significant for all traits except pollen grain size. The OCA mean square magnitude was considerably higher than SCA mean square for anther length and I OO-anther weight. The inverse was found for percent filled spikelets. It reveals additive gene effects for anther length, IOO-anther weight and dominance gene effects for percent filled spikelets. Basmati 198 displayed positive and significant general combining ability effects for anther length and IOO-anther weight. Basmati 370 was the best general combiner for percent filled spikelets. 4048 x Basmati 198, Basmati 370 x 4048 and Basmati 370 x Basmati 385 were the best specific combiners for anther length, 100-anther weight and percent filled spikelets respectively and are expected to contribute higher frequency of desirable plants than other crosses in subsequent generations.